2015
DOI: 10.1016/j.crwh.2015.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Chorioamnionitis due to Lactococcus lactis cremoris : A case report

Abstract: Lactococcus lactis cremoris is rarely involved in human pathology. A thirty two-year old pregnant woman with premature rupture of membrane history presented with chorioamnionitis due to L. lactis cremoris. She underwent an emergency caesarian section and was treated with antibiotics including the association of amoxicillin and clavulanic acid. She was completely recovered. This is the first case to our knowledge of chorioamnionitis due to this organism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 10 publications
1
5
1
Order By: Relevance
“…Concerning risk factors, some authors have suggested that immunocompromised subjects are more susceptible to the disease; however, we found only 26% of the cases, including ours, with a compromised immune status [4] , [10] , [19] , [21] , [27] , [30] . Although the evidence for increased susceptibility of pregnant women to infection is quite weak, immunological alterations during this period may impair pathogen clearance [31] .…”
Section: Clinical Discussioncontrasting
confidence: 84%
See 4 more Smart Citations
“…Concerning risk factors, some authors have suggested that immunocompromised subjects are more susceptible to the disease; however, we found only 26% of the cases, including ours, with a compromised immune status [4] , [10] , [19] , [21] , [27] , [30] . Although the evidence for increased susceptibility of pregnant women to infection is quite weak, immunological alterations during this period may impair pathogen clearance [31] .…”
Section: Clinical Discussioncontrasting
confidence: 84%
“…Therefore, its pathogenic potential is becoming well known by the scientific community. To our knowledge, our case is the second published case of Lactococcus lactis cremoris IUI and the 27th worldwide for other infectious sites [4] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] . Indeed, a review of the literature ( Table 1 ) allowed us to find the 26 cases published before ours and allowed us to highlight some of the features of this uncommon infection.…”
Section: Clinical Discussionmentioning
confidence: 71%
See 3 more Smart Citations